Association Between Enterovirus Infection and Type 1 Diabetes Risk: A Meta-Analysis of 38 Case-Control Studies - Wang, Kan; Ye, Fei; Chen, Yong; Xu, Jianxin; Zhao, Yufang; Wang, Yeping; Lan, Tian (Frontiers in Endocrinology, 2021)
Objective: The association between enterovirus infection and type 1 diabetes (T1D) is controversial, and this meta-analysis aimed to explore the correlation. Methods: PubMed, Embase, Web of Science, and Cochrane Database were searched from inception to April 2020. Studies were included if they could provide sufficient information to calculate odds ratios and 95% confidence intervals. All analyses were performed using STATA 15.1. Results: Thirty-eight studies, encompassing 5921 subjects (2841 T1D patients and 3080 controls), were included. The pooled analysis showed that enterovirus infection was associated with T1D (P < 0.001). Enterovirus infection was correlated with T1D in the European (P < 0.001), African (P = 0.002), Asian (P = 0.001), Australian (P = 0.011), and Latin American (P = 0.002) populations, but no conclusion could be reached fort in the North Americans. The association between enterovirus infection and T1D was detected in blood and tissue samples (both P < 0.001); no association was found in stool samples. Conclusion: Our findings suggest that enterovirus infection is associated with T1D.